Peningkatan Kecerdasan Matematis Logis Melalui Permainan Balok Geometri Pada Anak Usia Dini - Saqinatul Hasanah; Ansharul Fuqaha (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2023)
This stuff Sims to describe, 1) Logical mathematical intelligence abilities of children at PGRI Tamidung kindergarten, 2) Geometri block game technique in improving children's Logical mathematical intelligence skills in PGRI Tamidung kindergarten, 3) Increasing children's Logical mathematical intelligence abilities after applying geometric block games. To answer these problems researchers use classroom action research (PTK). The research model used adopts the opinion of Kurt Lewin in which there are four stayed, that id planning, action, observation, and reflection. The process of implementing this research is Collaborative and participatory between teachers, children, and other individuals involved in the learning process. The results of the analycis illustrator that there is an increase in children's Logical mathematical intelligence abilities using geometris block games. This can be seen from the initial value before and after the action is taken. Before the action was taken there was 0% with a very good developing category (BSB). After cycle I it reached 0%, and after continuing in cycle II it reached 76,92% with the BSB category. From the final score obtained in cycle II it has exceeded the agreed succes criteria limited between researchers and collabrators. So for the final results Achieved in cycle II, there is no need to hold cycle III.